Resilience of Tibetan pastoral system in modernisation - Xu, Haoyang (2009)
On the Tibetan Plateau, there is a long history of animal farming practices. Although Tibetan pastoralism had been successful in the past to support the population, the problems of increasing demand and impact in the face of more scarce resources and global climate change are challenging pastoralists. The problem is even more pronounced in the Tibetan Plateau’s unique natural and socioeconomic conditions.